2019
DOI: 10.3390/agronomy9100649
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Analysis of Nutrient Variations in Electrical Conductivity-Based Closed-Loop Soilless Culture Systems by Nutrient Replenishment Method

Abstract: In closed-loop soilless culture systems, variation in nutrients can lead to instability in the nutrient management and forced discharge of nutrients and water. Total nutrients absorbed by plants are replenished in an electrical conductivity-based closed-loop system, and fluctuation in electrical conductivity within a certain range around the initial value can be expected. However, this is not always observed in systems using conventional nutrient-replenishment methods. The objectives of this study were to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
(91 reference statements)
3
8
0
Order By: Relevance
“…However, the recent literature theoretically deduced a modified nutrient replenishment method for steady-state management of EC and experimentally demonstrated its effect ( Ahn and Son, 2019 ). Here, this study’s theoretical prediction on the effect of steady-state EC control was observed in the greenhouse experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the recent literature theoretically deduced a modified nutrient replenishment method for steady-state management of EC and experimentally demonstrated its effect ( Ahn and Son, 2019 ). Here, this study’s theoretical prediction on the effect of steady-state EC control was observed in the greenhouse experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding nutrient control principles under this condition may require a systems approach. Recently, a theoretical analysis study of a soilless culture system predicted a modified nutrient replenishment method and experimentally verified the theoretical prediction that a modified nutrient replenishment method could stabilize the fluctuations of some individual nutrients in the EC-based CL soilless culture (Ahn and Son, 2019). However, there is still little information on how the individual nutrient could be controlled in the EC-based CL soilless culture so far.…”
Section: Introductionmentioning
confidence: 95%
“…In the soilless culture system, the irrigation was controlled based on the integrated solar radiation of + and it followed the general greenhouse irrigation automation technique [11]. Nutrient and water transfers were made by referring to the nutrient transport model under substrate conditions [23] and the interconnection between the models was based on Ahn and Son's soilless culture system model [24].…”
Section: Simulation Analysis Of Nutrient Uptake Estimationmentioning
confidence: 99%
“…In the soilless culture 104 system, the irrigation was controlled based on the integrated solar radiation of + and it followed the 6 general greenhouse irrigation automation technique (Shin and Son, 2016). Nutrient and water transfers were made by referring to the nutrient transport model under substrate conditions (Silberbush et al, 2005), and the interconnection between the models was based on Ahn and Son's soilless culture system model (Ahn and Son, 2019).…”
Section: Simulation Analysis Of Nutrient Uptake Estimationmentioning
confidence: 99%